Synthesis, Characterization, Antibacterial and Antifungal Activity of Some Bis (1, 3, 4-oxadiazole) Polymer - Nawar Jamal Abdul Rada (Journal of Global Pharma Technology, 2020)
Pyridine-2, 6-dicarbohydrazide comp (2) was synthesized from ethanolic solution of diethyl pyridine-2, 6-dicarboxylate comp (1) with excess of hydrazine hydrate. Newly five polymers (P1-P5) were synthesized from reaction of pyridine-2, 6-dicarbohydrazide comp (2) with five different di carboxylic acid in the presence of poly phosphoric acid (PPA). The antibacterial activity of the synthesized polymers was screened against some gram positive and gram negative bacteria.  Antifungal activity of these polymers was evaluated in vitro against some yeast like fungi such as albicans (candida albicans). Polymers P3, P4 and P5exhibited highest antibacterial and antifungal against all microorganisms under test.Keywords: Bis 1, 3, 4-oxadiazole, Polymer, Antibacterial, Antifungal.